Optimal sizing of TCSC using ant colony optimization (ACO) technique for loss minimization - Abdullah, Mukhtaruddin (2008)
Power transmission loss of grid can be improved by upgrading or adding of new transmission circuit. TCSC offer a strong alternative for optimizing the transmission over power link, existing as well as new, by means intended for the control of power flow, improvement of stability, voltage profile management, power factor correction, and power losses. This thesis presents optimal sizing of Thyristor Controlled Series Capacitor (TCSC) using Ant Colony Optimization (ACO) technique for loss minimization in power system. The study involved the development of optimization engine to implement the TCSC installation. So that cost can be minimized. TCSCs are the control variables in this scheme. Prior to optimizing the TCSCs, size, tests were conducted on the IEEE 57-bus reliability test system, producing promising result.